Strategic consequences of emotional misrepresentation in negotiation: The blowback effect. - Campagna, Rachel L.; Mislin, Alexandra A.; Kong, Dejun Tony; Bottom, William P. (Journal of Applied Psychology, 2016)
Recent research indicates that expressing anger elicits concession making from negotiating counterparts. When emotions are conveyed either by a computer program or by a confederate, results appear to affirm a long-standing notion that feigning anger is an effective bargaining tactic. We hypothesize this tactic actually jeopardizes postnegotiation deal implementation and subsequent exchange. Four studies directly test both tactical and strategic consequences of emotional misrepresentation. False representations of anger generated little tactical benefit but produced considerable and persistent strategic disadvantage. This disadvantage is because of an effect we call "blowback." A negotiator's misrepresented anger creates an action-reaction cycle that results in genuine anger and diminishes trust in both the negotiator and counterpart. Our findings highlight the importance of considering the strategic implications of emotional misrepresentation for negotiators interested in claiming value. We discuss the benefits of researching reciprocal interdependence between 2 or more negotiating parties and of modeling value creation beyond deal construction to include implementation of terms. (PsycINFO Database Record